Comparative study on the flexural strengthening of RC beams using EB CFRP sheets, NSM CFRP bars, P-SWRs, and their combinations. Issue 5 (April 2021) - Zeng, Yihua; Li, Xinghua; Ali Ahmed, Amira Hamdy; Wu, Gang
The externally bonded (EB) carbon fiber reinforced polymer (CFRP), near-surface-mounted (NSM) CFRP and the prestressed steel wire ropes (P-SWRs) has been proven to be feasible and reliable flexural strengthening methods for concrete structures. However, debonding issues in EB CFRP sheets (or NSM CFRP bars) and space requirements for edge and spacing clearance of NSM CFRP bars (or P-SWRs) has limited the application of these three strengthening techniques. Therefore, the combinations of these methods need to be investigated and clarified. In this paper, experimental investigations on the flexural performances of seven concrete beams are presented, in which three of the beams were separately strengthened with EB CFRP sheets, NSM CFRP bars, and P-SWRs, respectively, and three of the beams were combinedly strengthened with two of the three techniques. Test results demonstrated that the flexural performances of beams strengthened with the combination with EB CFRP sheets, NSM CFRP bars, and P-SWRs are between the flexural performances of the beams strengthened with the corresponding individual strengthening techniques. It is found that the P-SWRs is favorable for combinations. In case the P-SWRs was combined with EB CFRP sheets or NSM CFRP bars for strengthening, the cracking load was increased to more than 230% and the maximum ultimate load-bearing capacity was increased to 150% when compared with the control beam. The debonding which occurred more or less in the beams strengthened with EB CFRP sheets or NSM CFRP bars or their combination was successfully eliminated by using the combination strengthening technique with P-SWRs. Also, the combination of P-SWRs with EB CFRP sheets or NSM CFRP bars is also favorable to improve the ductility of strengthened beams.